2001
DOI: 10.1111/j.1574-6976.2001.tb00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Lantibiotics: structure, biosynthesis and mode of action

Abstract: The lantibiotics are a group of ribosomally synthesised, post-translationally modified peptides containing unusual amino acids, such as dehydrated and lanthionine residues. This group of bacteriocins has attracted much attention in recent years due to the success of the well characterised lantibiotic, nisin, as a food preservative. Numerous other lantibiotics have since been identified and can be divided into two groups on the basis of their structures, designated type-A and type-B. To date, many of these lant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
328
0
18

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(352 citation statements)
references
References 235 publications
(387 reference statements)
6
328
0
18
Order By: Relevance
“…Bacteriocin-associated antibacterial activities have been observed both in vitro and in vivo at concentrations in the nanomolar range and develop against Gram-positive bacteria closely related to the producing strain. Several bacteriocins act upon the cell envelopes of target pathogens, and others are active within the cell and affect gene expression (47,48). Pores and ion channels formed in the cytoplasmic membrane of the target microbial cell and the subsequent leakage of intracellular components and protein production are the typical modes of bacteriostatic and bactericidal activities, despite the structural and physicochemical differences observed between the different classes of bacteriocins.…”
Section: Gastrointestinal Microbiotamentioning
confidence: 99%
“…Bacteriocin-associated antibacterial activities have been observed both in vitro and in vivo at concentrations in the nanomolar range and develop against Gram-positive bacteria closely related to the producing strain. Several bacteriocins act upon the cell envelopes of target pathogens, and others are active within the cell and affect gene expression (47,48). Pores and ion channels formed in the cytoplasmic membrane of the target microbial cell and the subsequent leakage of intracellular components and protein production are the typical modes of bacteriostatic and bactericidal activities, despite the structural and physicochemical differences observed between the different classes of bacteriocins.…”
Section: Gastrointestinal Microbiotamentioning
confidence: 99%
“…3). The remaining 171-bp gene sequence (6,225 Da, assuming all cysteines are reduced) was predicted to encode the putative active bacteriocin. The amino acid sequence showed that the bacteriocin contained a repeated CysXaa-Xaa motif (where Xaa is any amino acid) at the C terminus.…”
Section: Isolation and Identification Of Microorganisms Producing Antmentioning
confidence: 99%
“…Bacteriocins are ribosomally synthesized AMPs produced by prokaryotes that are bactericidal and/or bacteriostatic against organisms often, but not always, related to the producer strain (4). These metabolites are heterogeneous compounds produced by various Gram-positive and Gram-negative microorganisms (3,(5)(6)(7). Bacteriocins are classified into different classes (8).…”
mentioning
confidence: 99%
“…Due to the vast differences among leader peptide sequences, the findings of studies of the actual function of the leader peptide sequence during lantibiotic biosynthesis have been inconsistent. It has been suggested that the leader peptide sequence is a signal for transport, inactivates the peptide to protect the producing strain, and provides recognition for PTM enzymes (20)(21)(22). Conserved motifs that provide a reasonable basis for the classification of lantibiotics are found in some leader peptides.…”
mentioning
confidence: 99%